Engaging Reluctant Readers in a French Immersion Classroom - Amanda Borton Capina; Gregory Bryan (Arizona State University, 2017)
Reading engagement is like a puzzle consisting of many pieces to emplace for successful engagement to occur. The author, a French Immersion teacher/researcher, found that many of her grade one reluctant readersthose students who could read but chose not toapproached reading with some pieces of the puzzle. They had strategies and knowledge but lacked motivation to engage in reading. This led to the question: How do reluctant readers in my classroom respond to practices designed to increase their motivation to read? This study is qualitative-oriented action research. The author fulfilled the dual role of teacher and researcher as she introduced and taught seven classroom practices to see which ones helped the reluctant readers to increase their motivation to read. By applying multiple data collection methods the teacher/researcher set out to record what reluctant readers had to say about each of the classroom practices.